TARI REJANG LILIT DALAM UPACARA DEWA YAJÑA SEBAGAI DAYA TARIK PARIWISATA BERBASIS BUDAYA DI TANAH EMBET LOMBOK BARAT - Ni Nyoman Harnika (Widya Sandhi, 2022)
The art of rejang lilit dance performed by Hindu women in Dusun Tanah Embet as acomplement to the dewa yajña ceremony has a very important position in carrying outHindu religious ceremonies. In this regard, this rejang lilit dance also has the potential tobe a cultural-based tourist attraction, especially related to the implementation of Hinduism.This study was designed in a qualitative descriptive method in order to describe theperformance of the rejang lilit dance in relation to the implementation of Hinduism andalso as a tourist attraction. Based on the results of this study, two findings were foundrelated to the performance of the rejang lilit dance. First, the rejang lilit dance as one ofthe sacred dance types owned by the Hindu community in Dusun Tanah Embet is veryimportant in completing the dewa yajña ceremony activities which are carried out intemples managed by the Hindu community of Dusun Tanah Embet. This rejang lilit dance61is a form of embodiment of a sense of devotion to Ida Sang Hyang Widhi Wasa and at thesame time embodies the splendor of the implementation of the dewa yajña ceremony.Second, the performance of the rejang lilit dance in a series of dewa yajña ceremonies alsohas the potential to attract tourists visiting the area. The rejang lilit dance performance atthe time of the melasti ceremony on the beach has the potential to be watched by touristswho are traveling in that location. In this regard, it is necessary to think ahead that thispotential can be used as an aspect in the development of cultural tourism related to theimplementation of Hinduism